College Writing Skills - Langan, John (Mc Graw Hill)
Highly regarded and used by countless students, this effective rhetoric/handbook/reader is ideal for writing courses that focus on the essay. The sixth edition features Langan's renowned clear writing style and a wide range of writing assignments and activities that reinforce the four essentials of good writing: unity, support, coherence, and sentence skills. College Writing Skills with Readings comes packaged with a free student CD-ROM, a free registration card for access to the Online Learning Center, and a free user's guide to help students gain the maximum benefit from the text and electronic materials. "I long ago lost count of the number of instructors who have told me that the four bases really work. When you explain the four bases to students and make the bases really clear with a lot of activities, students get it." - John Langan.